If you were my bunny - McMullan, Kate (New York : Scholastic Inc, 1996)
A mother tells her baby how she would care for it if were a bunny, a kitten, or other animal infant; she then sings a lullaby about each baby animal.
Keywords: Babies-Fiction; Mother and child-Fiction; Bedtime-Fiction; Animals-Infancy-Fiction; Lullabies